Smart Cities Digital Transformation: Funded by Tufidco in Tamil Nadu (Global Journal of Management and Business Research, 2023)
In India the smart cities projects were implemented by Indian government In Tamil Nadu many states are selected to convert cities into smart cities TUFIDCO is providing financial assistance to smart cities projects The digital Transformation is the vital part in smart cities projects The main aim of Tamil Nadu Urban Finance and Infrastructure Development Corporation Limited mission is to provide financial assistance and guidance to Local Bodies Corporations Boards Authorities and parastatal agencies for their development projects An intelligent city refers that provides all the facilities a city needs such as education electricity transportation green environments good governance and information technologies To put it simply smart cities improve the quality of life The selected Smart Cities are Chennai Coimbatore Madurai Thanjavur Salem Vellore Tiruppur Thoothukudi Tirunelveli Tiruchirappalli and Erode in Tamil Nadu Researchers obtain data from secondary sources In order to carry out this research the researcher should analyze the funding provided to the government by TUFIDCO to implement smart cities in Tamil Nadu
Keywords: TUFIDCO; smart cities; cost; project; financial assistance; digital transformation